2019
DOI: 10.1002/ece3.5263
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection drives leaf divergence in experimental populations ofSenecio lautusunder natural conditions

Abstract: Leaf morphology is highly variable both within and between plant species. This study employs a combination of common garden and reciprocal transplant experiments to determine whether differences in leaf shape between Senecio lautus ecotypes has evolved as an adaptive response to divergent ecological conditions. We created a synthetic population of hybrid genotypes to segregate morphological variation between three ecotypes and performed reciprocal transplants where this hybrid population was transplanted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Our results are consistent with two previous studies using reciprocal transplant experiments at a reduced geographical scale to test for the adaptive feature of leaf shape ( Ferris and Willis, 2018 ; Richards et al, 2019 ), both of which found dissected leaves performed better in dry environments. However, unlike the consistent adaptation to drought, previous studies found that lobed/dissected leaves are likely adaptive in either particularly hot or cold habitats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with two previous studies using reciprocal transplant experiments at a reduced geographical scale to test for the adaptive feature of leaf shape ( Ferris and Willis, 2018 ; Richards et al, 2019 ), both of which found dissected leaves performed better in dry environments. However, unlike the consistent adaptation to drought, previous studies found that lobed/dissected leaves are likely adaptive in either particularly hot or cold habitats.…”
Section: Discussionsupporting
confidence: 92%
“…However, leaf-shape variation between or within natural populations or closely related species can be controlled by genetic loci ( Kidner and Umbreen, 2010 ) and thus may also be influenced by neutral processes, such as genetic drift and restricted gene flow. Yet few studies have detected genetic signatures of natural selection on leaf shape and related variation to putative adaptive function ( Ferris, 2019 ; but see Bright and Rausher, 2008 ; Campitelli and Stinchcombe, 2013 ; Ferris and Willis, 2018 ; Richards et al, 2019 ), the adaptive feature of leaf shape still needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of using Senecio as a model system to overcome such difficulties is two‐fold. First, many Senecio species show evidence of recent rapid adaptive radiation, providing the opportunity to characterize the strength and direction of selection during the early stages of adaptive diversification using transplant experiments (Walter et al , ; Richards et al , ). Second, Senecio species often display high levels of intraspecific variation, often with a well‐defined structure among populations (i.e.…”
Section: Integrating Studies Of Genotype Phenotype and Fitnessmentioning
confidence: 99%
“…In many cases, species also produce viable hybrids (unlike highly divergent taxa), allowing their use in multigeneration artificial hybridization experiments (e.g. Richards et al , ; Walter et al , ; Wilkinson et al , ). These crosses can be used to recreate genetic and phenotypic variation that is currently absent in natural populations and may reflect earlier stages of divergence among sister species.…”
Section: Integrating Studies Of Genotype Phenotype and Fitnessmentioning
confidence: 99%